It is currently 25 Jun 2017, 09:25

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# If x2 + 3x + c = (x + a)(x + b) for all x, what is the value

Author Message
Manager
Joined: 11 Jan 2007
Posts: 196
Location: Bangkok
If x2 + 3x + c = (x + a)(x + b) for all x, what is the value [#permalink]

### Show Tags

08 Jun 2007, 20:45
00:00

Difficulty:

(N/A)

Question Stats:

0% (00:00) correct 0% (00:00) wrong based on 0 sessions

### HideShow timer Statistics

This topic is locked. If you want to discuss this question please re-post it in the respective forum.

Q10:
If x2 + 3x + c = (x + a)(x + b) for all x, what is the value of c ?
(1) a = 1
(2) b = 2
_________________

cool

Intern
Joined: 03 Aug 2006
Posts: 22

### Show Tags

08 Jun 2007, 21:04
C?

I solved it to c=3. Is this correct?
SVP
Joined: 01 May 2006
Posts: 1796

### Show Tags

09 Jun 2007, 01:14
(D) for me

We have:
x^2 + 3x + c
= (x + a)(x + b)
= x^2 + (a+b)*x + a*b

So,
o c = a*b
o a+b = 3

Thus, if we know one of a,b, we can conclude on both values of a & b and then on the value of c.
VP
Joined: 08 Jun 2005
Posts: 1145

### Show Tags

09 Jun 2007, 01:54
Fig wrote:
(D) for me

We have:
x^2 + 3x + c
= (x + a)(x + b)
= x^2 + (a+b)*x + a*b

So,
o c = a*b
o a+b = 3

Thus, if we know one of a,b, we can conclude on both values of a & b and then on the value of c.

Very clever Fig - but what about a=0 and b=3 ?

x^2+3x+0 = (x+0)(x+3)

SVP
Joined: 01 May 2006
Posts: 1796

### Show Tags

09 Jun 2007, 04:23
KillerSquirrel wrote:
Fig wrote:
(D) for me

We have:
x^2 + 3x + c
= (x + a)(x + b)
= x^2 + (a+b)*x + a*b

So,
o c = a*b
o a+b = 3

Thus, if we know one of a,b, we can conclude on both values of a & b and then on the value of c.

Very clever Fig - but what about a=0 and b=3 ?

x^2+3x+0 = (x+0)(x+3)

I dont understand your question ... The case analysed by the 2 given statments brings a = 2, b=1 & c = 2.

Even if we want to consider a=0 & b=3.... we have the value of c = 0.

Would u perhaps reformulate ?
VP
Joined: 08 Jun 2005
Posts: 1145

### Show Tags

09 Jun 2007, 04:39
Fig wrote:
KillerSquirrel wrote:
Fig wrote:
(D) for me

We have:
x^2 + 3x + c
= (x + a)(x + b)
= x^2 + (a+b)*x + a*b

So,
o c = a*b
o a+b = 3

Thus, if we know one of a,b, we can conclude on both values of a & b and then on the value of c.

Very clever Fig - but what about a=0 and b=3 ?

x^2+3x+0 = (x+0)(x+3)

I dont understand your question ... The case analysed by the 2 given statments brings a = 2, b=1 & c = 2.

Even if we want to consider a=0 & b=3.... we have the value of c = 0.

Would u perhaps reformulate ?

Sorry for that - I now understand. Thanks Fig well done !

SVP
Joined: 01 May 2006
Posts: 1796

### Show Tags

09 Jun 2007, 05:09
KillerSquirrel wrote:
Fig wrote:
KillerSquirrel wrote:
Fig wrote:
(D) for me

We have:
x^2 + 3x + c
= (x + a)(x + b)
= x^2 + (a+b)*x + a*b

So,
o c = a*b
o a+b = 3

Thus, if we know one of a,b, we can conclude on both values of a & b and then on the value of c.

Very clever Fig - but what about a=0 and b=3 ?

x^2+3x+0 = (x+0)(x+3)

I dont understand your question ... The case analysed by the 2 given statments brings a = 2, b=1 & c = 2.

Even if we want to consider a=0 & b=3.... we have the value of c = 0.

Would u perhaps reformulate ?

Sorry for that - I now understand. Thanks Fig well done !

ok
09 Jun 2007, 05:09
Display posts from previous: Sort by